Association of Reduced Type IX Collagen Gene Expression in Human Osteoarthritic Chondrocytes With Epigenetic Silencing by DNA Hypermethylation. Issue 11 (November 2014) - Imagawa, Kei; de Andrés, María C.; Hashimoto, Ko; Itoi, Eiji; Otero, Miguel; Roach, Helmtrud I.; Goldring, Mary B.; Oreffo, Richard O. C.
<x xml:space="preserve">Abstract</x> Objective To investigate whether the changes in collagen gene expression in osteoarthritic (OA) human chondrocytes are associated with changes in the DNA methylation status in the COL2A1 enhancer and COL9A1 promoter. Methods Expression levels were determined using quantitative reverse transcription–polymerase chain reaction, and the percentage of DNA methylation was quantified by pyrosequencing. The effect of CpG methylation on COL9A1 promoter activity was determined using a CpG‐free vector; cotransfections with expression vectors encoding SOX9, hypoxia‐inducible factor 1α (HIF‐1α), and HIF‐2α were carried out to analyze COL9A1 promoter activities in response to changes in the methylation status. Chromatin immunoprecipitation assays were carried out to validate SOX9 binding to the COL9A1 promoter and the influence of DNA methylation. Results Although COL2A1 messenger RNA (mRNA) levels in OA chondrocytes were 19‐fold higher than those in the controls, all of the CpG sites in the COL2A1 enhancer were totally demethylated in both samples. The levels of COL9A1 mRNA in OA chondrocytes were 6, 000‐fold lower than those in controls; 6 CpG sites of the COL9A1 promoter were significantly hypermethylated in OA patients as compared with controls. Treatment with 5‐azadeoxycitidine enhanced COL9A1 gene expression and prevented culture‐induced hypermethylation. In vitro methylation decreased COL9A1 promoter activity. Mutations in the 5 CpG sites proximal to the transcription start site decreased COL9A1 promoter activity. Cotransfection with SOX9 enhanced COL9A1 promoter activity; CpG methylation attenuated SOX9 binding to the COL9A1 promoter. Conclusion This first demonstration that hypermethylation is associated with down‐regulation of COL9A1 expression in OA cartilage highlights the pivotal role of epigenetics in OA, involving not only hypomethylation, but also hypermethylation, with important therapeutic implications for OA treatment.